2021
DOI: 10.1007/s00384-021-03872-3
|View full text |Cite
|
Sign up to set email alerts
|

Same-day discharge after appendectomy for acute appendicitis: a systematic review and meta-analysis

Abstract: Purpose Patients presenting with acute appendicitis are usually hospitalized for a few days for appendectomy and postoperative recovery. Shortening length of stay may reduce costs and improve patient satisfaction. The purpose of this study was to assess the safety of same-day discharge after appendectomy for acute appendicitis. Methods A systematic review was performed according to PRISMA guidelines. A literature search of EMBASE, Ovid MEDLINE, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 43 publications
3
31
2
3
Order By: Relevance
“…It might be that same day discharge is possible because of this lower risk and those with wound infection/complication would have required additional management and/or observation, thereby necessitating stay at the hospital. These findings are in agreement with a previous review by Elisabeth et al ( 14 ) that looked at studies done in both adult and pediatric populations and indicated that same-day discharge after laparoscopic appendectomy in patients with uncomplicated appendicitis is relatively safe and is not associated with a higher risk of readmission, complications, or unplanned hospital visits. One of the major drawbacks of the earlier review was that it did not provide stratified findings based on adult and pediatric subjects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It might be that same day discharge is possible because of this lower risk and those with wound infection/complication would have required additional management and/or observation, thereby necessitating stay at the hospital. These findings are in agreement with a previous review by Elisabeth et al ( 14 ) that looked at studies done in both adult and pediatric populations and indicated that same-day discharge after laparoscopic appendectomy in patients with uncomplicated appendicitis is relatively safe and is not associated with a higher risk of readmission, complications, or unplanned hospital visits. One of the major drawbacks of the earlier review was that it did not provide stratified findings based on adult and pediatric subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Studies, in both adult and pediatric populations, have examined the possibility of the same-day discharge (SDD). A recent review was conducted to assess the safety of the same-day discharge after appendectomy in adults and children with acute appendicitis ( 14 ). The review included 17 studies and performed a comparative analysis between same-day discharge and non-same day discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to reduce LOS after laparoscopic appendectomy may relieve pressure on hospital bed capacity, decrease healthcare costs, and improve treatment satisfaction. Many studies have evaluated the safety and feasibility of early discharge after laparoscopic ap-pendectomy [7]. However, as with any surgical procedure, approximately 2% to 23% of laparoscopic appendectomy patients experience postoperative complications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis from 2021 suggested that same-day discharge following laparoscopic appendectomy for uncomplicated appendicitis is safe and does not increase the risk of readmission, complications, or unplanned hospital visits. Moreover, it can reduce costs and improve the patient’s satisfaction [ 37 ].…”
Section: Introductionmentioning
confidence: 99%